Identification of a Novel α-herpesvirus Associated with Ulcerative Stomatitis in Donkeys - Martella, Vito (Emerg Infect Dis, 2020)
An outbreak of ulcerative stomatitis was observed in a donkey (Equus asinus) dairy herd. Similar lesions were also observed on the dams’ udders and, sporadically, in genital areas. The lesions typically resolved in 1–3 weeks. An α-herpesvirus, Varicellovirus, genetically related to equid herpesvirus type 3, was identified.